2010
DOI: 10.1055/s-0030-1258505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TRIP and Analysis of Phosphate Salt Impurities

Abstract: The chiral phosphoric acid TRIP, a useful Brønsted acid catalyst, easily becomes contaminated with metal impurities in the form of phosphate salts during synthesis. This significantly reduces the content of free acid in the product which can hamper the catalytic activity. Methods to easily judge whether TRIP contains mainly the free acid or phosphate salts are presented, using 1 H NMR spectroscopy or a simple pH test. An improved synthetic protocol for TRIP was established that reliably produces the free acid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 7 publications
1
102
0
2
Order By: Relevance
“…The pK a and general applicability of chiral phosphoric acids made them attractive candidates for the development of an enantioselective bromocycloetherification process using a catalytic amount of a chiral Brønsted acid, potentially in conjunction with a Lewis base co‐catalyst . This line of research led to the development of an enantioselective bromocycloetherification reaction of 5‐arylpentenols ( 1a , 1d , 1e , 1f , 1g , 1h , 1i , 1j , 1k , 1l , 1m ) cooperatively catalyzed by the combination of the versatile chiral phosphoric acid TRIP ( 2a ) and the achiral Lewis base Ph 3 P=S, producing chiral tetrahydrofurans ( 3a , 3d , 3e , 3f , 3g , 3h , 3i , 3j , 3k , 3l , 3m ) and tetrahydropyrans ( 4a , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m ) (Fig. ) .…”
Section: Introductionmentioning
confidence: 99%
“…The pK a and general applicability of chiral phosphoric acids made them attractive candidates for the development of an enantioselective bromocycloetherification process using a catalytic amount of a chiral Brønsted acid, potentially in conjunction with a Lewis base co‐catalyst . This line of research led to the development of an enantioselective bromocycloetherification reaction of 5‐arylpentenols ( 1a , 1d , 1e , 1f , 1g , 1h , 1i , 1j , 1k , 1l , 1m ) cooperatively catalyzed by the combination of the versatile chiral phosphoric acid TRIP ( 2a ) and the achiral Lewis base Ph 3 P=S, producing chiral tetrahydrofurans ( 3a , 3d , 3e , 3f , 3g , 3h , 3i , 3j , 3k , 3l , 3m ) and tetrahydropyrans ( 4a , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m ) (Fig. ) .…”
Section: Introductionmentioning
confidence: 99%
“…The pKa and general applicability of BINOL-derived phosphoric acids made them attractive candidates to initiate this study. 8 …”
mentioning
confidence: 99%
“…The synthetic route to PA 1 to 4 resembled the known synthesis of catalysts 1 . Starting from optically pure (R)‐BINOL 7 , the hydroxyl was protected by methyl groups, which could afford desired product 8 in high yield.…”
Section: Resultsmentioning
confidence: 95%
“…Different metal catalysts have been screened, and we found that Ni (PPh 3 ) 2 Cl 2 was suitable for Kumada cross‐coupling, and Pd (dppf)Cl 2 was compliant with the Suzuki coupling. Removal of the methyl groups with BBr 3 gave the compounds 11c and 11d . The phosphate group was introduced by reacting with POCl 3 , hydrolyzing with water and washing with 2 M HCl, which afforded pure PA 3 and PA 4 after recrystallization .…”
Section: Resultsmentioning
confidence: 99%